Medication Error pada Tahap Prescribing, Transcribing, Dispensing dan Administration - Eka Ananda Laksana Putri; Asep Sukohar; Ervina Damayanti (Medula, 2023)
Medication Error is any error that occurs in the treatment process, endangers the patient and can actually be prevented. According to WHO, the number of incidents of medication errors shows that this is a global problem. This error occurs both in the process of prescribing (prescribing), reading the prescription (transcribing), preparation to drug delivery (dispensing), as well as in the process of drug use (administering). In this journal review, issues related to Medication Errors are collected and then reviewed again to see definitions, terminology, events, influencing factors, ways of prevention and legal consequences related to Medication Errors. Medication error can be a very fundamental clinical problem. Factors that influence Medication Error include the complexity of clinical cases, lack of knowledge of doctors and pharmacists, factors related to drugs, communication, workload and unsupportive work systems. In prevention, pharmacists have an important role because they collaborate directly with doctors who write prescriptions. Automation and computers, rules and policies, standards and protocols, checklists and double check systems, and greater caution and vigilance can be used to reduce medication Error. Patients are protected by law because they are consumers of health services. The relationship between doctors and patients involves legal aspects, namely civil and criminal. Criminal law only applies to errors and negligence if the patient dies or becomes disabled as a result of the medical treatment provided whereas civil lawsuits can be filed when the patient suffers a loss even if the fault is minor.